2002
DOI: 10.1093/toxsci/68.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream and Sidestream Cigarette Smoke Inhibit Growth and Angiogenesis in the Day 5 Chick Chorioallantoic Membrane

Abstract: The purpose of this study was to test the hypothesis that components in mainstream (MS) and sidestream (SS) cigarette smoke inhibit growth and angiogenesis using the chick chorioallantoic membrane (CAM). Varying doses of whole or gas-phase MS and SS smoke solutions were placed on day 5 CAMs, and their effects on angiogenesis were evaluated on day 6. All parameters evaluated (CAM area, major blood vessel area, major blood vessel diameter, blood vessel pattern formation, and capillary plexus formation) were inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…Our data do not eliminate the possibility that the CD44 protein or ligand or the tenascin protein was targeted by sidestream smoke. Increased expression of tenascin in CAMs treated with mainstream smoke and 3-ethylpyridine (current study) correlated with inhibition of CAM growth and vascular development (Ji et al 2002;Melkonian et al 2002), supporting the conclusion that too much tenascin can inhibit these processes. This conclusion is also supported by our observations that high levels of tenascin in CAMs were associated with mesodermal blood vessels that did not migrate to the ectoderm and with the endoderm, which is located opposite the direction of vessel migration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data do not eliminate the possibility that the CD44 protein or ligand or the tenascin protein was targeted by sidestream smoke. Increased expression of tenascin in CAMs treated with mainstream smoke and 3-ethylpyridine (current study) correlated with inhibition of CAM growth and vascular development (Ji et al 2002;Melkonian et al 2002), supporting the conclusion that too much tenascin can inhibit these processes. This conclusion is also supported by our observations that high levels of tenascin in CAMs were associated with mesodermal blood vessels that did not migrate to the ectoderm and with the endoderm, which is located opposite the direction of vessel migration.…”
Section: Discussionsupporting
confidence: 78%
“…We subsequently used the more versatile day 5-6 CAMs to show that both mainstream and sidestream cigarette smoke solutions and specific individual toxicants in smoke inhibit overall CAM growth (Ji et al 2002;Melkonian et al 2002) and that some smoke toxicants, such as 3-ethylpyridine, significantly inhibit growth at picomolar doses (Ji et al 2002). In day 5-6 CAMs, smoke solutions also disrupted normal development of major blood vessels and impaired formation of the capillary plexus by inhibiting both vasculogenesis and migration of mesodermal blood vessels to the plexus .…”
Section: Introductionmentioning
confidence: 99%
“…Solutions of tobacco smoke can also be made by drawing smoke through culture medium and testing the resulting solution at various doses . When working with solutions, whole smoke can be tested, or the particulate phase (collected on a filter) and gas phase (portion that passes through the filter) can be collected and tested separately (Melkonian et al, 2002). In some studies, smoke has been drawn directly over cultured cells or culture medium has been exposed to smoke for variable lengths of time to produce smoke conditioned medium (Soghomonians et al, 2004;Vidal et al, 2006).…”
Section: Testing Tobacco Products In Vitromentioning
confidence: 99%
“…This led to the hypothesis that nicotine and other tobacco carcinogens might be playing a direct role in the induction and progression of human lung cancers (4,5,13). While there is no evidence that nicotine contributes to the induction of tumors, it has been demonstrated that nicotine promotes the growth of solid tumors in vivo, suggesting that nicotine might be contributing to the progression of tumors already initiated (4,14). Indeed, studies by Song et al have shown that nAChRs expressed on lung carcinoma form a part of an autocrine-proliferative network that facilitates the growth of neoplastic cells (13,15); other studies have demonstrated that nicotine can promote the growth of colon, gastric, and lung cancers (4,5,13,16,17).…”
Section: Introductionmentioning
confidence: 99%